Pengaruh Sari Buah Nanas (Ananas Cosumus l.) Terhadap Total Plate Count (TPC) Dan Derajat Keasaman (pH) Daging Ayam Broiler - Widhowati, Dyah; Wiranata, Ferian Pandu; Kurnianto, Ady; Yanestria, Sheila Marty (VITEK : Bidang Kedokteran Hewan, 2021)
The aimed of this study was to determine the effectivity of pineapple essence (Ananas Comosus) as a natural reservative in chicken meat with parameters of total colony of bacteria and pH. The experimental design used completely randomized design with 4 treatments and 6 replications. The treatments applied were P0 as a control, P1 (25% pineapple essence), P2 (50% pineapple essence), and P3 (100% pineapple essence). The parameters of this study were the total colony of bacteria (TPC) and pH. The results of the statistical analysis showed that the total colony of bacteria in meat were P0 = 4,2 x104, P1 = 2,0 x 104, P2 = 1,9 x 104, dan P3 = 1,2 x 104. pH in chicken meat P0 = 5,0 ± 0,17a, P1 = 4,2 ± 0,05b, P2 = 4,0 ± 0,08c, dan P3 = 3,9 ± 0,10d.. The results of this study showed significant difference in chicken meat containing pineapple essence on total colony of bacteria and pH. The most effective result was chicken meat with 100% pineapple essence.